PENGARUH MEDIA PEMBELAJARAN E-MOKACINO (MONOPOLI KEBUDAYAAN DAN CIRI KHAS INDONESIA) TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPAS POKOK BAHASAN INDONESIAKU KAYA RAYA KELAS 5 SDN POHSANGIT KIDUL 1 - Amalia Hikmatul Jannah; Didit Yulian Kasdriyanto; Ryzca Siti Qomariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low cognitive learning outcomes of students in the subject “Indonesiaku Kaya Raya” (My Rich Indonesia) in the IPAS class of grade V at SDN Pohsangit Kidul 1, which was caused by the lack of interactive and contextual learning media. To overcome this, the researcher used E-MOKACINO (Electronic Media on Indonesian Culture and Characteristics) to improve students' understanding. This study is quantitative in nature, employing a pre-experimental method and a One Group Pretest-Posttest Design, involving 14 students in the 2024/2025 academic year. Data were collected through observation, tests, and documentation. Statistical analysis results showed a significant improvement in students' learning outcomes after using E-MOKACINO. The Paired Sample T-Test revealed a significance value of 0.000 < 0.05, thus rejecting H0 and accepting H1. In conclusion, the E-MOKACINO learning media significantly influences the improvement of students' cognitive learning outcomes.